KORELASI BUNDLE PHLEBITIS DENGAN KEJADIAN PHLEBITIS DI RUANG RAWAT INAP - Susiyanti Susiyanti; Krisma Yuntari Gusti Ayu; Artana I Wayan; Nara Kusuma A.A.Ngurah (Universitas Prima Indonesia, 2022)
The incidence of phlebitis in Tk.II Udayana hospital was 4.88% higher than the 2013 standard of the Indonesian Ministry of Health, which was <1.5%, even though the hospital had prepared a Phlebitis Bundle Standard Operating Procedure (SOP). This study aims to determine the correlation between bundle phlebitis and the incidence of phlebitis in the inpatient room of Tk. II Udayana. This study was a quantitative observational study with a correlational method and a cross-sectional design. The study involved 81 samples, namely patients who were treated in five inpatient rooms. Data collection nurses' compliance with SOP and the incidence of phlebitis in patients using observation sheets. Data were analyzed using Rank Spearman correlation. It was found that 45 nurses (55.6%) were obedient in carrying out the phlebitis bundle and there were 54 people (66.7%) patients who did not experience phlebitis. There was a positive correlation between bundle phlebitis and the incidence of phlebitis (p0.001 <0.05). It is recommended that the hospital provide assistance to the nurse in charge when providing intravenous infusion therapy by applying the standard operating procedure (SOP) of the phlebitis bundle.